Magnetically Aligned Supramolecular Hydrogels. Issue 50 (24th October 2014) - Wallace, Matthew; Cardoso, Andre Zamith; Frith, William J.; Iggo, Jonathan A.; Adams, Dave J.
Abstract The magnetic‐field‐induced alignment of the fibrillar structures present in an aqueous solution of a dipeptide gelator, and the subsequent retention of this alignment upon transformation to a hydrogel upon the addition of CaCl2 or upon a reduction in solution pH is reported. Utilising the switchable nature of the magnetic field coupled with the slow diffusion of CaCl2, it is possible to precisely control the extent of anisotropy across a hydrogel, something that is generally very difficult to do using alternative methods. The approach is readily extended to other compounds that form viscous solutions at high pH. It is expected that this work will greatly expand the utility of such low‐molecular‐weight gelators (LMWG) in areas where alignment is key.